Benefício de prestação continuada para a população migrante - Kidricki, Tiago Beck (2025)
This dissertation is linked to the research line “Constitutional Jurisdiction and Democracy”, of the Stricto sensu Graduate Program in Law – PPGDireito, of the University of Passo Fundo (UPF) - Passo Fundo/RS, related to the New Paradigms of Law, being in tune and in harmony with these fields of knowledge. Among the concrete actions of social assistance in Brazil, the administration of the Continuous Benefit Payment (BPC) stands out, which is governed by the Organic Law of Social Assistance (Law nº 8742/93). The creation of this benefit is provided for in the Federal Constitution of 1988, and is regulated by the Organic Law of Social Assistance (LOAS), Law No. 8742, of December 1993. Therefore, because it is aimed at individuals in situations of economic and social vulnerability, which aims to ensure their survival, the BPC is closely related to the preservation of human dignity and the maintenance of fundamental rights, in addition to stimulating social solidarity and the reduction of poverty. In view of this, the objective of this Dissertation is to analyze the right to BPC for the migrant population in Brazil, in light of the Brazilian constitutional, infraconstitutional and jurisprudential framework that governs the matter, investigating the main obstacles that hinder access by migrants, from bureaucratic barriers to socioeconomic and cultural challenges. Methodologically, the research adopts a qualitative approach, classified as exploratory, of a bibliographic nature. In the investigation phase, the deductive method was applied, while in the data treatment stage, the hypothetical-deductive scientific method was used. It is important to emphasize that this is still a case study, encompassing descriptive research. As a result, it was possible to understand that the inclusion of migrants in Brazil's social assistance system represents progress not only for these citizens, but for the entire community. When the country allocates resources to promote equality and respect human dignity, it establishes a favorable scenario for social and economic development. By being welcomed and valued, migrants have the opportunity to contribute significantly to Brazil's progress, collaborating in the construction of a more prosperous, supportive and diverse nation. This reflection highlights that Brazilian social assistance, based on the constitutional principles of equality and dignity, should serve as a means of inclusion and social justice for all, regardless of origin. By promoting the integration of the migrant population and guaranteeing the right to social protection, Brazil is moving towards a society that values every human being and recognizes the importance of a support system that is accessible and inclusive, promoting general well-being. This requires careful reflection on social security policies and the obstacles that hinder the full realization of their rights.